Association of chronic pain with physical function and mortality among older adults in rural Malaysia / Chan Yee Mang - Chan, Yee Mang (2020)
Older adults are postulated to double in 2017 and 2050 worldwide, including Malaysia. Various challenges are related to ageing population, including poor physical functioning and increase number of chronic diseases. Chronic pain is often associated with chronic disease. Chronic pain affects almost one third of the world’s adult population and higher prevalence reported among older adults. Evidence suggests that chronic pain has undesirable consequences on physical, mental health and premature mortality. In lowand middle-income countries, there are limited studies examining the consequences of chronic pain on physical function and premature mortality. The aim of this study is therefore to determine the association between chronic pain and physical disability, functional limitations and five-year mortality. The design of the study was a secondary analysis of existing cohort data in Kuala Pilah, Negeri Sembilan, Malaysia. Baseline assessments were conducted from November 2013 to February 2014. Twelve months follow-up data were collected from December 2014 to February 2015. The study population was older adults 60 years of age and above living in Kuala Pilah for a minimum period of 12 months prior to data collection. Respondents were excluded if they were not Malaysian citizens, living in nursing homes, admitted to hospital during the interview, refused to participate or had severe cognitive impairment. Logistic regression was used to examine cross-sectional associations between baseline chronic pain and outcomes of interest. Generalized Estimating Equation was used to examine longitudinal associations between baseline chronic pain and outcomes of interest. Cox Proportional Hazard model was used to examine the association between chronic pain and five-year mortality. The prevalence of chronic pain was 21.1% (95%CI 19.4, 22.8). Chronic pain was associated with higher risk of ADL disability (RR 2.14; 95%CI 1.38, 3.46) and IADL disability (RR 1.30; 95%CI 1.04, 1.62). However, chronic pain was not associated with higher risk of slow walking speed (RR 1.01, 95%CI 0.79, 1.29) and low handgrip strength iv (RR 1.15; 95%CI 0.94, 1.40). The five-year mortality rate was higher in respondents with chronic pain (26.24%) compared to those with no chronic pain (18.51%). But, no significant association was observed (HR 1.09; 95%CI 0.84, 1.41). Early detection of chronic pain and appropriate pain management are important for the management of high chronic pain distribution among older adults in Malaysia. Effective interventions and preventive strategies are crucial to reduce the risk of ADL and IADL disabilities among older adults with chronic pain. Recommendation on adequate level of physical activity could be one of the preventive strategies to reduce the risk of ADL disability, IADL disability and five-year mortality. It is hoped that the findings of this study will be used to improve chronic pain management in the existing guidelines for pain management in local setting. Keywords: Older adults, chronic pain, physical disability, functional limitations, mortality